Factors that Influence Student Achievement (Mawapres) in Learning Motivation - Zahid Zufar At Thaariq; Dedi Kuswandi; Risma Chulashotud Diana; Ukhfi Shelinawati (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
This study examines the effect of learning motivation of high achieving students at Universitas Negeri Malang. Learning motivation has an important role in the lecture process. Learning motivation is an impetus in a conscious effort to make changes in cognitive, affective and psychomotor aspects. So it takes students who are able to increase their motivation for achievement in order to be an example for other students. Therefore researchers are interested in studying research related to learning motivation and ways of learning from outstanding students. The object of research studied was outstanding students at Universitas Negeri Malang. The research method used is quantitative data obtained through the distribution of questionnaires in the Google form. The results of this study reveal the motivation to learn and how to learn from each respondent who is an outstanding student at Universitas Negeri Malang. The results of the research are expected to be a reference in increasing learning motivation for other students. The results of the research are expected to be a reference in increasing learning motivation for other students. It seen by explained about the desires of respondents in learning. From the picture, it is explained that 75 percent of respondents want to learn because they are trying to find experience, 13 percent of respondents say they want to learn because they are trying to find a new channel (friends) with the same vision, 4 percent say the first and third choice, 4 percent say they have a character who is hungry for learning and wants learn whenever and wherever and 4 percent say they want to learn